2019
DOI: 10.5397/cise.2019.22.2.106
|View full text |Cite
|
Sign up to set email alerts
|

Acute Displaced Fracture of Lateral Acromion after Reverse Shoulder Arthroplasty: A Case Report and Surgical Technique

Abstract: Acromial fractures are well-documented complications subsequent to reverse shoulder arthroplasty (RSA), and most appear as stress fractures with no history of single trauma. To date, no study has reported the occurrence of acute displaced acromial fracture due to sudden strong deltoid contraction during heavy work. Displacement of the fracture results in a challenging surgery since it is difficult to obtain adequate fixation in thin and osteoporotic bones. We report a rare case of acute displaced acromial frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…One study was identified from review references of the identified articles [ 29 ]. In total, nine clinical studies with 18 acromion or scapular spine fractures met the inclusion and exclusion criteria and were included in this review [ 16 , 17 , 18 , 29 , 30 , 31 , 32 , 33 , 34 ]. A detailed flow diagram of the search results is provided under Figure 2 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…One study was identified from review references of the identified articles [ 29 ]. In total, nine clinical studies with 18 acromion or scapular spine fractures met the inclusion and exclusion criteria and were included in this review [ 16 , 17 , 18 , 29 , 30 , 31 , 32 , 33 , 34 ]. A detailed flow diagram of the search results is provided under Figure 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The majority of patients were female (83.3), the average age was 74.2 years (range, 63–83 years) and the mean follow-up was 13.4 months (range, 2–24 months). Time from RSA to fracture fixation was not reported in two case reports [ 16 , 29 ]. These cases underwent fixation with a lateral locking plate with two lag screws and a 1/3 tubular plate, respectively ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations